2021
DOI: 10.3390/w13182603
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Complexation of Fluoroquinolone and β-Lactam Antibiotics with Iron (III) on the Photodegradation under Solar Light and UVC Light

Abstract: Antibiotics elimination by some photochemical processes involves ferric ions, but little is discussed about the fundamental aspects of complexation effects on their degradation. This study compares the photodegradation of two fluoroquinolones, three β-lactams, and their ferric complexes in deionized water. The complexed antibiotics were more recalcitrant than the free antibiotics to the solar light action (the photodegradation rate constants diminished by more than 50%). To better study the photodegradation, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Moreover, the mixture of the antibiotic and the ferric ions induced an intense yellow coloration of the solution. These results evidenced the formation of a CIP-Fe 3+ complex [ 33 ]. However, no interaction between ferrous ions and CIP was observed ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the mixture of the antibiotic and the ferric ions induced an intense yellow coloration of the solution. These results evidenced the formation of a CIP-Fe 3+ complex [ 33 ]. However, no interaction between ferrous ions and CIP was observed ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, no interaction between ferrous ions and CIP was observed ( Figure S3 ). Recent studies have also reported that the interaction between fluoroquinolones (CIP belongs to this antibiotics class) and ferric ions leads to the formation of stable complexes [ 33 , 34 ]. It can be noted that CIP has the keto-carbonyl moiety (structure with a higher number of lone electron pairs), which favors the interaction between this fluoroquinolone and ferric ion through chelation [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(F)Q photolytic rate constants and degradation pathways are highly pH and cation dependent. They exhibit the greatest photolysis rates at neutral pH, when the neutral form (and zwitterionic when also presenting amino groups) is the most abundant [ 8 , 9 ], whereas regarding the cations, it is variable, depending on the type of cation and (F)Q, respectively, forming diverse (F)Q–metal complexes with different stabilities, observing photolytic enhancement [ 10 ] or hindrance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%